Pengambilan Keputusan Dalam Pemilihan Penerima Bantuan Sosial Dengan Metode Multi-Factor Evaluation Process - Muhammad Azhari; Ahmad Iqbal; Sindy Khairi Purba; Putrama Alkhairi (Bulletin of Artificial Intelligence, 2025)
Social assistance program is one of the government initiatives to reduce poverty level in Indonesia. In Simalungun Regency, Karang Anyar Village, the large amount of recipient data that needs to be processed can slow down the distribution of aid to people in need. This study aims to develop a system that can support social assistance facilitators in determining the right recipients quickly and accurately. The method used in this study is the Multi-Factor Evaluation Process (MFEP), which is expected to be able to identify recipients more efficiently. The data analyzed in this study consists of 25 prospective social assistance recipients obtained from social assistance facilitators in Karang Anyar Village. The assessment criteria for aid recipients include the presence of family members of Early Childhood, Pregnant Women, Elderly, People with Disabilities, High School Children (SMA), Middle School Children (SMP), and Elementary School Children (SD). The MFEP stages include determining the weight for each criterion, assigning a value to each factor, calculating the evaluation weight, and summing all evaluation weights to obtain the final value as a basis for decision making. Data processing on 25 potential aid recipients revealed that 24 were eligible and 6 were ineligible. The results of this data processing using the MFEP method, compared with manual data from social assistance facilitators in Simalungun, Karang Anyar Village, showed a 100% accuracy rate for decision-making. With this level of accuracy, the MFEP method has been proven to assist the decision-making process in selecting appropriate social assistance recipients in Simalungun Regency, Karang Anyar Village.